2000
DOI: 10.1097/00005650-200006000-00004
|View full text |Cite
|
Sign up to set email alerts
|

One Thousand Health-Related Quality-of-Life Estimates

Abstract: This comprehensive review of QOL data should lead to more consistent use of QOL weights and thus more comparable cost-effectiveness analyses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
385
0
3

Year Published

2003
2003
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 604 publications
(398 citation statements)
references
References 27 publications
10
385
0
3
Order By: Relevance
“…Large-scale studies have used questionnaires to establish utility values for a variety of health states. Arthritis has consistently been shown to have a utility value near 0.7 [30][31][32][33]. Knee and hip arthroplasties have been shown to increase quality of life weightings close to normal values.…”
Section: Effectivenessmentioning
confidence: 99%
“…Large-scale studies have used questionnaires to establish utility values for a variety of health states. Arthritis has consistently been shown to have a utility value near 0.7 [30][31][32][33]. Knee and hip arthroplasties have been shown to increase quality of life weightings close to normal values.…”
Section: Effectivenessmentioning
confidence: 99%
“…The effectiveness of each procedure or health state is measured in utility units that incorporate subjective measures of wellness or quality of life [11]. Each health state in the model is assigned a utility value along a continuum of 1.0 equaling perfect health and 0.0 equaling death based on quality of wellbeing index scores [9,10,23,24,26]. The utility for each health state then is multiplied by the number of years a patient experiences that health state and is reported in QALY.…”
Section: Introductionmentioning
confidence: 99%
“…Strength of preference estimates via the VAS were close to TTO values. The scores by all three methods were generally in the range of those for serious medical problems, such as stroke, heart attack, and cancer (30). Furthermore, quality-of-life scores are similar to those for major depression but slightly higher than for disorders involving psychoses (bipolar disorder and schizophrenia).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, quality-of-life scores are similar to those for major depression but slightly higher than for disorders involving psychoses (bipolar disorder and schizophrenia). In a comprehensive review paper, Tengs and Wallace (30) reported median quality-of-life scores for an episode of depression and of severe bipolar disorder or schizophrenia of .77 and .65, respectively.…”
Section: Discussionmentioning
confidence: 99%